Respiratory acidosis and alkalosis - Kundan Mittal; H K Aggarwal; N Rungta; Vinayak Patki (Wolters Kluwer Medknow Publications, 2021)
Respiratory illnesses and failure are common in pediatric population compared to adults due to anatomical and physiological differences in respiratory system. Respiratory acidosis is commonly seen in intensive care settings and needs immediate attention. Treatment depends on underlying pathology and mechanical ventilation. Respiratory alkalosis is least common only mainly iatrogenic or child is hyperventilating.